Neusa Welter Bocchese e as leituras da cidade de Antônio Prado, RS: representação de um patrimônio histórico - Galvani, Mara Aparecida Magero (My University, 2018)
This thesis focuses on the work of Neusa Welter Bocchese, an artist born in Vacaria in 1936, who lives in Antonio Prado, a city that until today is the theme of her production, which begun in 1983. In order to analyze her representations of the city, we selected 64 images of her work, distributed in eight groups, in order to evaluate, from Burke (2017), the role of these images as historical evidences and as testimonies of the Italian-Brazilian cultural process, and to what extent her work contributes to the preservation of the identity of the Northeast Region of Rio Grande do Sul, considering the reception, production and thematic factors. Looking from a cultural history perspective, our analysis is subsidized by the methodology of representation related to reading practices proposed by Chartier (2002). We also draw on the theoretical assumptions of Stüben (2013), on the idea of the region as a literary landscape, transposed here into the field of art and, on Nora (1993), regarding places of memory, including contributions of literature, through the novels of Calvin (1990) and Pozenato (2000). Since identity is marked by symbolic means, it was possible, from the intersection of the artist's readings about the city of Antonio Prado, and the readings we make of the meanings of her representations, to identify that she explicitly explains the discourse of the tipping, but, above all, rewrites new texts from the first, highlighting the differences that classify a regional cultural group. In the representations of what was lived by others, in the past tense, and of the lived by Bocchese in the present time, the artist sometimes maintains similarity with the city, sometimes dismantles it, reworking it in new arrangements, but without breaking its connection with her. Pozenato (2003) observes that, while certain manifestations that identify a culture remain, that culture exists, but in the political vision of cultural preservation it might not be necessary to preserve the physical monument itself, since preservation of memory would suffice. Thus, we can infer that, just as Antonio Prado is a place of memory, Bocchese's work emerged from the context associated with Italian immigration, which becomes a place of memory. Her representations are interpretations of the cultural practices of a group, forming another one, even before the official, by IPHAN, in 1989. Moreover, her representations prestige the non-preserved symbolic elements in other RCI cities, which are then materialized in her work – witness and identity of the region.
Esta tese focaliza a obra de Neusa Welter Bocchese, artista nascida no Município de Vacaria, Rio Grande do Sul, em 1936, que reside em Antônio Prado, cidade que até hoje é tema de sua produção, iniciada em 1983. Com o objetivo de analisar suas representações da cidade, selecionamos 64 imagens de sua obra, distribuídas em oito grupos, para, sob a perspectiva de Burke (2017), avaliar o papel dessas imagens como evidências históricas e como testemunhos do processo cultural Itália-Brasil e, ainda, em que medida sua obra contribui para a preservação da identidade da região Nordeste do Rio Grande do Sul, considerando os fatores recepção, produção e temática. Olhando de uma perspectiva da história cultural, nossa análise é subsidiada pela metodologia acerca da representação ligada às práticas de leitura proposta por Chartier (2002). Também nos baseamos nos pressupostos teóricos de Stüben (2013), quanto à ideia de região como paisagem literária, aqui transposta para o campo da arte, e de Nora (1993), no que concerne aos lugares de memória, incluindo, ainda, as contribuições da literatura, por meio dos romances de Calvino (1990) e Pozenato (2000). Visto que a identidade é marcada por meios simbólicos, foi possível, a partir do cruzamento das leituras da artista acerca da cidade de Antônio Prado e das leituras que fazemos dos significados de suas representações, identificar que ela explicita o discurso do tombamento, mas, sobretudo, reescreve novos textos a partir do primeiro, sublinhando as diferenças que classificam um grupo cultural regional. Nas representações do vivido por outros, no tempo passado, e do vivido por Bocchese no tempo presente, a artista ora mantém similaridade com a cidade, ora a desmonta, reelaborando-a em novos arranjos, mas sem romper sua ligação com ela. Referindo-se às edificações e aos monumentos, Pozenato (2003) observa que, enquanto permanecem determinadas manifestações que identificam uma cultura, aquela cultura existe, mas na visão política de preservação cultural talvez não fosse necessário conservar o próprio monumento físico, já que a preservação da memória seria suficiente. Assim, podemos inferir que, do mesmo modo que Antônio Prado é lugar de memória, a obra de Bocchese surgida do/no contexto associado à imigração italiana torna-se lugar de memória. Suas representações são interpretações das práticas culturais de um grupo, constituindo-se em outro tombamento, antes mesmo do oficial, pelo IPHAN, em 1989. E, ainda, suas representações presentificam os elementos simbólicos não preservados em outras cidades da RCI, que são, então, materializados em sua obra – testemunho e identidade da regiã
Keywords: Bocchese, Neusa Welter; Patrimônio histórico - Antônio Prado (RS); Leitura; Memória; Identidade; Historical heritage - Antônio Prado (Brazil); Reading; Memory; Identity (Psychology)